As lost as a pun in a corpus: an investigation into noncanonical phraseological occurrences in large corpora and translation - Brezolin, Adauri (Tradterm, 2021)
Although it might appear contradictory to investigate noncanonical phraseological combinations in corpora, corpus linguistics research has revealed that they exceed canonical forms in number (Philip 2008). This paper intends to discuss the idea of fixedness by analyzing variant forms of idioms, and if they qualify as wordplay. The Web, our data source, is employed for collecting such noncanonical occurrences in both English and Portuguese using keywords on the Google Search Engine. Our discussion mainly draws on studies relating to fixed phrases (Kjellmer 1991; Granger & Paquot 2008; Tagnin 2013); phraseological skeletons (Renouf & Sinclair 1991; Philip 2008), and idiom transformations (Veisbergs 1997; Barta 2005). Due attention is also given to search queries of nonstandard forms of fixed expressions in corpora (Philip 2008), and the translation of idiom-based wordplay (Veisbergs 1997; Brezolin 2020)